2016
DOI: 10.1161/circresaha.115.307961
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Ribonucleic Acids (RNA) Enter the Stage in Cardiovascular Disease

Abstract: Inflammatory and ischemic cardiovascular diseases, especially atherosclerosis and myocardial infarction, remain the number one cause of death in the Western world, whereas the therapeutic options currently available are still limited. Several recent findings have indicated that nucleic acids, particularly extracellular ribosomal RNA and micro-RNAs, significantly contribute to the adverse outcome of atherosclerosis, myocardial infarction, and other cardiovascular diseases. Extracellular RNAs act as novel danger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 93 publications
1
71
1
Order By: Relevance
“…In addition to regulating the expression of mRNAs and thus protein expression within cells, miRNAs can also be secreted to the extracellular compartment, as can ribosomal RNA. These extracellular RNAs adversely affect outcomes in I/R by acting as damage-associated molecular patterns (DAMPs) and as cofactors for activation of inflammatory cascades and thrombosis (899). Indeed, myocardial I/R is associated with significant release of RNA, including several miRNAs, primarily by cardiac myocytes, although endothelial cells, fibroblasts, and vascular smooth muscle cells also contribute (105, 133).…”
Section: Epigenetic Changes Contribute To I/r Injurymentioning
confidence: 99%
“…In addition to regulating the expression of mRNAs and thus protein expression within cells, miRNAs can also be secreted to the extracellular compartment, as can ribosomal RNA. These extracellular RNAs adversely affect outcomes in I/R by acting as damage-associated molecular patterns (DAMPs) and as cofactors for activation of inflammatory cascades and thrombosis (899). Indeed, myocardial I/R is associated with significant release of RNA, including several miRNAs, primarily by cardiac myocytes, although endothelial cells, fibroblasts, and vascular smooth muscle cells also contribute (105, 133).…”
Section: Epigenetic Changes Contribute To I/r Injurymentioning
confidence: 99%
“…Cardiomyocyte‐derived HMGB1 may serve as an important early stimulus, triggering the inflammatory reaction following myocardial infarction. IL‐1α, extracellular RNAs, HSPs and members of the S100 family may also contribute to activation of myocardial inflammation. Immune cells may be important cellular targets of alarmins in the infarcted myocardium.…”
Section: Immune Cells In Cardiac Repairmentioning
confidence: 99%
“…Recent work has identified extracellular RNA (exRNA) as a heterogeneous class of secreted cofactors in bodily fluids that can contribute to coagulation, blood vessel permeability, cell–cell signaling, tumor progression, and inflammation. They can be single or double-stranded, and can originate from internal cells or from antigenic sources, such as invading bacteria or viruses [71, 72]. As the only known ribonuclease in bodily fluids with high, nonspecific ribonucleolytic activity, RNase 1 might be a natural regulator of exRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, we found that some mammalian RNase 1 homologs not only degrade dsRNA efficiently, but also enter endosomes readily, potentially mediated by interactions with cell-surface glycans. Human RNase 1, in particular, might be especially well adapted to degrade antigenic exRNA both within endosomes and in the extracellular space, suggesting an important role for human RNase 1 in regulating processes like coagulation and inflammation [72]. The amino acid sequence of human RNase 1 is identical to that of the Neanderthal enzyme [74], indicative of its biological role being established in a common ancestor at least 550,000 years ago.…”
Section: Discussionmentioning
confidence: 99%